Unusual structural features of the 5S ribosomal RNA from Streptococcus cremoris. - Neimark, H (1983)
The nucleotide sequence of the 5S ribosomal RNA of Streptococcus cremoris has been determined. The sequence is 5' (sequence in text) 3'. Comparison of the S. cremoris 5S RNA sequence to an updated prokaryotic generalized 5S RNA structural model shows that this 5S RNA contains some unusual structural features. These features result largely from uncommon base substitutions in helices I, II and IV. Some of these unusual structural features are shared by several of the known 5S RNA sequences from mycoplasmas. However, the characteristic bloc of deletions found in helix V of these mycoplasma 5S RNAs is not present in the 5S RNA of S. cremoris.